Assistance in Planning Wirogunan Village Land Assets as a Progressive Village Tourism Destination in Sukoharjo Regency - Priyono, Kuswaji Dwi; Setiawan, Wisnu; Sari, Dewi Novita (Universitas Muhammadiyah Surakarta, 2024)
The assets of Wirogunan village in Kartasura District in the form of 5 plots of land covering an area of 3.5 ha have not been utilized optimally, so it looks dirty with the growth of weeds and strewn with unmanaged rubbish. The Community service Team at Muhammadiyah University of Surakarta has agreed with BUMDes Wirogunan Village officials on the importance of planning the use of the village's assets with the main aim of being a Village Tourism Destination based on a study of the toponymy of the origin of the name Wirogunan. The potential and development plans are divided into 5 main areas (clusters), consisting of: cluster 1 (village government center area, meeting hall, culinary market and sports), cluster 2 (area of the historical grave of the Duke of Wiroguno and his spring), cluster 3 ( fruit garden, waste management and sports), cluster 4 (new Kartasura terminal supporting interconnection of tourist destinations), and cluster 5 (main road to the cemetery and interconnection terminal for tourist destinations). Assistance is provided regarding the potential for developing Web-based tourist destinations and their supporters and waste management as a requirement for Green Tourism. The results of assisting village officials understand the importance of a master plan for village tourism destinations connected to the Village Web and village waste management towards a Progressive Tourism Village.